1995
DOI: 10.1128/iai.63.10.3759-3764.1995
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between virulence of Mycobacterium avium strains and induction of tumor necrosis factor alpha production in infected mice and in in vitro-cultured mouse macrophages

Abstract: We studied the ability of two Mycobacterium avium strains with different virulences to induce tumor necrosis factor alpha (TNF) synthesis by mouse resident peritoneal macrophages (RPM) in vitro in an experiment to look for a possible correlation between virulence and this TNF-inducing capacity. The low-virulence strain, 1983, induced significantly higher production of TNF by RPM than did the high-virulence strain, ATCC 25291. TNF neutralization during culture of infected RPM resulted in enhancement of growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…It has been reported that less virulent mycobacteria are more sensitive to TNF. 71 We found adequate TNF responses in the liver as well as in isolated human or mouse macrophages (data not shown), so given the high influx of neutrophils and macrophages to the spleen from 1 week post infection we would have expected a higher production of inflammatory cytokines. Concomitant induction of anti-inflammatory IL-10 has previously been found to negatively influence the secretion of TNF and IFN-c in response to mycobacterial infection compared with other Gram-positive or Gram-negative microbes in human peripheral blood monocytes.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that less virulent mycobacteria are more sensitive to TNF. 71 We found adequate TNF responses in the liver as well as in isolated human or mouse macrophages (data not shown), so given the high influx of neutrophils and macrophages to the spleen from 1 week post infection we would have expected a higher production of inflammatory cytokines. Concomitant induction of anti-inflammatory IL-10 has previously been found to negatively influence the secretion of TNF and IFN-c in response to mycobacterial infection compared with other Gram-positive or Gram-negative microbes in human peripheral blood monocytes.…”
Section: Discussionmentioning
confidence: 76%
“…In CD14+/+ Mw, the highly virulent strain TMC724 always induced less TNF secretion than SE01, the strain of intermediate virulence, regardless of the dose used for stimulation, a ®nding previously reported for other M. avium isolates differing in virulence. 32 Of note, the dose required to elicit in CD14x/x bone marrow-derived Mw a response equivalent to that in CD14+/+ Mw was at least 10-fold higher for both strains tested 6 hr after infection ( Fig. 1a, 1b).…”
Section: Resultsmentioning
confidence: 97%
“…It has previously been noted that M. avium strains of differing virulence induce secretion of different amounts of TNF from Mw in vivo. 32 Our data extend these ®ndings and show that strains of both high and intermediate virulence induce TNF in a CD14-dependent manner.…”
Section: Discussionmentioning
confidence: 96%
“…3). On the contrary, Sarmento and Appelberg (47) and Eriks and Emerson (22) found that the low-virulence M. avium strains induced more intensive TNF-a production than the high-virulence M. avium bacilli did. However, they were using resident peritoneal or bone marrow-derived macrophages, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The microbicidal activity of macrophages against MTB and other mycobacteria has also been shown to be regulated by the TNF-oc alone or in synergy with other cytokines (5, 6,47). Furthermore, TNF-sa production in vivo may lead to granuloma formation, which limits bacterial dissemination within the host (52).…”
mentioning
confidence: 99%